Efficacy of a universal smoking cessation intervention initiated in inpatient psychiatry and continued post-discharge: A randomised controlled trial. (April 2017) - Metse, Alexandra P; Wiggers, John; Wye, Paula; Wolfenden, Luke; Freund, Megan; Clancy, Richard; Stockings, Emily; Terry, Margarett; Allan, John; Colyvas, Kim; Prochaska, Judith J; Bowman, Jenny A
Objective: Interventions are required to redress the disproportionate tobacco-related health burden experienced by persons with a mental illness. This study aimed to assess the efficacy of a universal smoking cessation intervention initiated within an acute psychiatric inpatient setting and continued post-discharge in reducing smoking prevalence and increasing quitting behaviours. Method: A randomised controlled trial was undertaken across four psychiatric inpatient facilities in Australia. Participants ( N = 754) were randomised to receive either usual care ( n = 375) or an intervention comprising a brief motivational interview and self-help material while in hospital, followed by a 4-month pharmacological and psychosocial intervention ( n = 379) upon discharge. Primary outcomes assessed at 6 and 12 months post-discharge were 7-day point prevalence and 1-month prolonged smoking abstinence. A number of secondary smoking-related outcomes were also assessed. Subgroup analyses were conducted based on psychiatric diagnosis, baseline readiness to quit and nicotine dependence. Results: Seven-day point prevalence abstinence was higher for intervention participants (15.8%) than controls (9.3%) at 6 months post-discharge (odds ratio = 1.07, p = 0.04), but not at 12 months (13.4% and 10.0%, respectively; odds ratio = 1.03, p = 0.25). Significant intervention effects were not found on measures of prolonged abstinence at either 6 or 12 months post-discharge. Differential intervention effects for the primary outcomes were not detected for any subgroups. At both 6 and 12 months post-discharge, intervention group participants were significantly more likely to smoke fewer cigarettes per day, have reduced cigarette consumption by ⩾50% and to have made at least one quit attempt, relative to controls. Conclusions: Universal smoking cessation treatment initiated in inpatient psychiatry and continued post-discharge was efficacious in increasing 7-day point prevalence smoking cessation rates and related quitting behaviours at 6 months post-discharge, with sustained effects on quitting behaviour at 12 months. Further research is required to identify strategies for achieving longer term smoking cessation.